2021
DOI: 10.3389/fimmu.2020.594620
|View full text |Cite
|
Sign up to set email alerts
|

IL-15 Upregulates Telomerase Expression and Potently Increases Proliferative Capacity of NK, NKT-Like, and CD8 T Cells

Abstract: Interleukin-15 (IL-15) is a cytokine that has been shown to expand CD8 T cell and natural killer (NK) cell populations, and therefore has potential for potentiating adoptive immune cell therapy for cancer. Previously, IL-15 has been shown to induce proliferation of CD8 memory T cells through activation of telomerase. Here, we investigated whether telomerase is also activated during the IL-15 mediated proliferation of NK and NKT-like (CD56+CD3+) cells. We also examined the extent that each of the three signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…The proliferation of NK cells is impacted by IL-7, IL-15, and 41BB ( 47 , 48 , 68 ). We noted that NKB cells have higher levels of transcripts leading to IL-7R, IL-2Rβ (which is also the beta chain receptor for IL-15), and 41BB but also to MKi67 than do NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…The proliferation of NK cells is impacted by IL-7, IL-15, and 41BB ( 47 , 48 , 68 ). We noted that NKB cells have higher levels of transcripts leading to IL-7R, IL-2Rβ (which is also the beta chain receptor for IL-15), and 41BB but also to MKi67 than do NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory has shown that IL-15 is the only protein among a panel of several cytokines that was able to expand and activate immune cells in vitro; this effect was increased when prostate cancer cells were present (Sakellariou et al, 2020). We have also shown that IL-15 was more potent in activating and expanding NK cells than IL-2 (Watkinson et al, 2020). Moreover, in in vivo studies, we have shown induction of cell death and improved mice survival when a membranelocalizing cytotopically modified IL-15 was injected directly into prostate tumors (Papaevangelou et al, 2020).…”
Section: Introductionmentioning
confidence: 93%
“…However, telomerase reverse transcriptase activity is normally downregulated in differentiated somatic cells to prevent their uncontrolled proliferation or malignant transformation. Nevertheless, in a number of cases telomerase reactivation is observed in physiological conditions, for example, in lymphocytes stimulated for robust proliferation [ 21 , 22 , 23 ]. The core of telomerase holoenzyme is represented by two key components necessary for its reverse transcriptase activity: telomerase RNA component (TERC) and telomerase reverse transcriptase (TERT).…”
Section: Telomere Structure and The Role In Dna Damage Responsementioning
confidence: 99%